Strategi Pemasaran Industri Rumah Tangga Pengolahan Ubi Kayu - Iriana, Putri; Facrizal, Riza; Sembiring, Jefri (MuJAgri: Musamus Journal of Agribusiness, 2021)
The study aims to identify internal factors (strengths and weaknesses) and external (opportunities and threats) as well as formulate strategies necessary for the improvement of the household industry processing of cassava. The methods used are techniques of SWOT analysis and qualitative descriptive. The chosen strategy determination is done using QSPM matrix. The research was conducted in Kampung Wenda Asri Jagebob District in August – September 2019. The results showed that the IFAS factor (Internal Factor Summary) in the processing of cassava, namely the availability of raw materials, manpower has expertise, has a good price, lack of marketing network, season affects production, lack of Management system. Factor EFAS (external Factor Summary) in the production industry of cassava, namely the support of the village and community government is very good, high market opportunities, cassava processing certification, has a business license from the government. SWOT Analysis formulates 8 alternative of i.e. 1; Raw materials and manpower available supported by business license can increase production 2; Improve the marketing network by adding 3 business partners; Conducting internal business management ongoing training 4; Improving quality of cassava's ignition to expand market opportunities 5; The Government participates in Sweet potato processing industry by providing informal education assistance to the processing of cassava 6; Have the capital assistance to advance the results of processed cassava with good processed products 7; Governments provide government-controlled saprodi assistance in order to maximize the potency of the cassava processing industry 8; Enhance the production of cassava processing technology. Furthermore, the matrix of QSPM (Quantitative Strategic Planning Matrixs), there are 2 (two) alternatives that have the highest scoring value as the first strategy done in advance 1; The available raw materials and manpower are supported by a business license can increase production, the total score 4.78 and the most up-to-date strategy 2; The Government provides assistance in the control of the government in order to maximize the potency of cassava processing, total alternative score 1.16.